Порядок структурування бюджетів як складова технології бюджетного управління компанією - Давидюк, Т. В.; Демчук, Олена Миколаївна; Трачова, Дар'я Миколаївна; Davydiuk, T.; Demchuk, Olena; Trachova, Daria (Запоріжжя : Друкарня ТДАТУ, 2022)
UA: У статті проаналізовано варіанти структурування бюджету доходів та витрат підприємства, що забезпечує планування його фінансових результатів, формуючи різні сценарії ведення бізнесу для розробки заходів, що дозволяють знизити ризики. Серед варіантів структурування проаналізовано переваги та недоліки використання бухгалтерського підходу, обрання управлінського звіту про прибутки та збитки та експертного аналізу. EN: Among the budgets, the most important is the budget of income and expenses, which allows you to plan the target indicators of the company's activity, while forming various business scenarios and predicting financial results for each of them, taking into account possible risks. The purpose of writing the article is to research the content of the options for structuring the list of items of the budget of income and expenses of the enterprise existing in the practice of financial planning and to determine the rules for their selection, taking into account the information needs of the business, the requirements of the budgeting methodology and financial structure. You can structure a list of income and expense budget items using: 1) an accounting approach that involves using a list of expense and income items from an accounting guide to build an income and expense budget; 2) management's statement of profit and loss as a basis for the construction of a list of expense and income guides; 3) expert analysis, which involves the construction of a separate list of income and expense items specifically for the needs of the budgeting system, taking into accountall aspects of the enterprise's activity. The considered options for structuring the list of income and expenditure budget articles indicate that the choice of one of them will be determined by the information needs of the business, the requirements of the management accounting methodology of the enterprise and the formed financial structure. However, excessive detailing of items of income and expenses can lead to an increase in the time of entering information.
The procedure for structuring budgets as a component of the company's budget management technology
Keywords: управлінський облік; бюджетування; фінансова структура; центр відповідальності; бюджет доходів та витрат; структурування статей бюджету підприємства; managerial accounting; budgeting; financial structure; responsibility center; income and expenditure budget; structuring of enterprise budget articles